Peran Lembaga Keuangan Mikro Dalam Otonomi Daerah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Decentralization era is a momentum for mobilizing local resources to develop local capital. Microfinance is the key to capital formation at the local level, solve the big problem of poverty and empower people's socio economy. The strength of microfinance is based on people driven and it's sustainability. Microfinance will contribute broad based development and development through equity.